PENGARUH PIJAT BAYI TERHADAP KUALITAS TIDUR BAYI USIA 0-6 BULAN DI BPM MABAR MEDICA KECAMATAN MEDAN DELI MEDAN KOTA SUMATERA UTARA TAHUN 2022 - Stefani Anastasia Sitepu; Mutiara Dwi Yanti; Vitrilina Hutabarat; Marlen Sadrina Sitepu (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Baby massage isone type of stimulation that will simulate the development of structures and function of celss in the brain. Currently varrious therapiess have been developed, both therapeutic pharmalogical and non-pharmalogical. One therapy Non-pharmalogic to overcome the problem of sleeping babies is Baby Masaage. The aim to be achieved in thhis research is to find out the effect of infant massage on sleep quality for babies aged 0-6 month at BPM Mabar Medica Medan Deli District, North of Sumatera.. The samping technique with a total samle of 10 infants. This Research instrument use baby massage SOP and observations sheet. Data analized by using wilcoxon test we get that p-valuee 0,024 < 0,05. Thatnit can be concluded that from the test results was Ha accepted and Ho is rejected, so there is an effects of baby massage on slee quality baby age 0-6 months at BPM Mabar Medica, Medan Deli District, Medan City, North Sumatera in 2022.